2009
DOI: 10.3892/ijo_00000400
|View full text |Cite
|
Sign up to set email alerts
|

SiRNA of Frizzled-9 suppresses proliferation and motility of hepatoma cells

Abstract: Abstract. Frizzled (Fz), a receptor of Wnt ligands, plays key roles in liver carcinogenesis. Its expression was analyzed as part of a search for a target of molecular therapy for hepatocellular carcinoma (HCC) and hepatoblastoma (HB). Fz genes were analyzed by RT-PCR in HCC cell lines HLE, HLF, PLC/PRF/5, Huh-7 and Hep3B, HB cell lines Huh-6 and HepG2, HeLa cells, human normal fetal and adult liver. We transfected PLC/PRF/5, HLE, Huh-6, and HeLa cells with Fz9-small interfering RNA (Fz9-siRNA). Five days after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…It has been reported that the identified biomarkers are closely related to aging and ND ( Table 2 ; Salmerón et al, 2001 ; Hu et al, 2004 ; Katoh, 2008 ; Qiu and Ghosh, 2008 ; Fujimoto et al, 2009 ; Su et al, 2009 ; Kozarova et al, 2011 ; Euskirchen et al, 2012 ; Berwick and Harvey, 2014 ; Lopez-Pelaez et al, 2014 ; Alquézar et al, 2016 ; Chailangkarn et al, 2016 ; Densham et al, 2016 ; Husain et al, 2016 ; Pîrşcoveanu et al, 2017 ; Kurihara et al, 2019 ; Monteiro and Forti, 2019 ). Interestingly, these related functions (i.e., DNA damage repair response, mitochondrial dysfunction, or Ca ion homeostasis disorder), further indicated the imbalance of cellular homeostasis, and abnormal cell death was further induced across various ND types.…”
Section: Resultsmentioning
confidence: 97%
“…It has been reported that the identified biomarkers are closely related to aging and ND ( Table 2 ; Salmerón et al, 2001 ; Hu et al, 2004 ; Katoh, 2008 ; Qiu and Ghosh, 2008 ; Fujimoto et al, 2009 ; Su et al, 2009 ; Kozarova et al, 2011 ; Euskirchen et al, 2012 ; Berwick and Harvey, 2014 ; Lopez-Pelaez et al, 2014 ; Alquézar et al, 2016 ; Chailangkarn et al, 2016 ; Densham et al, 2016 ; Husain et al, 2016 ; Pîrşcoveanu et al, 2017 ; Kurihara et al, 2019 ; Monteiro and Forti, 2019 ). Interestingly, these related functions (i.e., DNA damage repair response, mitochondrial dysfunction, or Ca ion homeostasis disorder), further indicated the imbalance of cellular homeostasis, and abnormal cell death was further induced across various ND types.…”
Section: Resultsmentioning
confidence: 97%
“…The FZD9 expression was increased in colorectal cancer tissues than in normal tissues and expressed in hepatocellular carcinoma (HCC) cell line, but absent in normal fetal and adult liver tissues (31,32). Elsewhere, FZD9 knockdown reduced the cyclin D1 levels, migration, and cell proliferation in HCC cells (32).…”
Section: Discussionmentioning
confidence: 99%
“…The FZD9 expression was increased in colorectal cancer tissues than in normal tissues and expressed in hepatocellular carcinoma (HCC) cell line, but absent in normal fetal and adult liver tissues (31,32). Elsewhere, FZD9 knockdown reduced the cyclin D1 levels, migration, and cell proliferation in HCC cells (32). In contrast, non-small cell lung cancer cells with ectopic expression of Wnt7a/Fzd9 showed an increase in the PPARy activity and inhibited the transformation of growth suggesting an anti-tumorigenic effect (33).…”
Section: Discussionmentioning
confidence: 99%
“…In a more refined analysis, the miRWalk databases were used to determine validated targets miR-106b-5p genes involved in gastric carcinogenesis and 14 genes from this pathway were found: APC (regulator of the WNT signaling pathway), CCND1 (cyclin D1) CDKN1A (cyclin-dependent kinase inhibitor 1), E2F1, E2F2, E2F3 (transcription factor 1, 2, and 3, respectively), FZD9 (frizzled class receptor 9), MAPK1 (mitogen-activated protein kinase 1), MYC (proto-oncogene BHLH transcription factor), RB1 (transcriptional corepressor 1), SMAD4 (SMAD family member 4), TCF7L2 (transcription factor 7-like 2), TGFBR2 (transforming growth factor β receptor 2), and TP53 (tumor protein p53). Considering the main functions described in the process of carcinogenesis, these genes are involved in cell cycle regulation and tumor progression, cell growth, adhesion and migration, proliferation, differentiation, genome stability, DNA repair, and apoptosis [42][43][44][45][46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%